Kids vs. plastic : ditch the straw and find the pollution solution to bottles, bags, and other single-use plastics : how you can be a waste warrior! - Dorey, Martin (National Geographic kids., 2020)
Discusses the history of plastic and how it has polluted the environment and the oceans. Features ways to minimize plastic use, and profiles researchers, scientists, and activists who are fighting to protect the planet. Includes color photographs and activities.